Transparent substrate for liquid crystal devices and light control sheets
The transparent substrate for liquid crystal devices addresses the issue of physical damage during roll-to-roll manufacturing by using a hard coat layer and specific surface roughness conditions, resulting in enhanced alignment layer integrity and reduced haze.
Patent Information
- Application Number
- JP2021072532
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-04-22
AI Technical Summary
The manufacturing of transparent substrates for liquid crystal devices using roll-to-roll devices can cause physical damage to the alignment layer due to external forces, leading to defects and reduced alignment restriction force.
A transparent substrate configuration with an alignment layer formed on a base layer that includes a hard coat layer with a pencil hardness of F or higher, and surface roughness conditions that reduce frictional force and maintain alignment restriction force, thereby preventing physical damage to the alignment layer.
The proposed solution effectively suppresses physical damage to the alignment layer, maintains the alignment restriction force, and reduces haze, ensuring the integrity and performance of the transparent substrate in liquid crystal devices.
Smart Images

Figure 0007647289000001 
Figure 0007647289000002 
Figure 0007647289000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent substrate for a liquid crystal device and a light controlling sheet. [Background technology]
[0002] A reverse-type light-controlling sheet has a relatively low haze when no voltage is applied between the pair of conductive layers, and a relatively high haze when a voltage is applied between the pair of conductive layers. An example of a reverse-type light-controlling sheet includes a light-controlling layer containing liquid crystal molecules, a pair of conductive layers (transparent electrodes) sandwiching the light-controlling layer in the thickness direction of the light-controlling layer, and alignment films positioned between the light-controlling layer and the conductive layer (see, for example, Patent Document 1). In this light-controlling sheet, when no voltage is applied between the pair of conductive layers, the alignment layer vertically aligns the liquid crystal molecules. When a voltage is applied between the pair of conductive layers, the liquid crystal molecules are randomly oriented, causing multiple reflection of incident light at the interface between the polymer and the liquid crystal. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-45135 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in order to enable mass production of light-adjusting sheets, it is required that light-adjusting sheets and transparent substrates having an alignment layer can be manufactured using a roll-to-roll device. When a transparent substrate is manufactured using a roll-to-roll device, an external force acts on the transparent substrate and, in turn, on the alignment layer of the transparent substrate during transport of the transparent substrate by the roll-to-roll device, during winding of the transparent substrate using the roll-to-roll device, and during transportation of the wound transparent substrate, which may cause physical damage to the alignment layer. In this way, a new problem occurs in the transparent substrate having an alignment layer due to the use of a roll-to-roll device to manufacture the transparent substrate.
[0005] These points are not limited to transparent substrates for light controlling sheets, but are also common to transparent substrates for other liquid crystal devices manufactured using a roll-to-roll apparatus. [Means for solving the problem]
[0006] The transparent substrate for a liquid crystal device of the present invention includes an alignment layer that regulates an alignment direction of liquid crystal molecules included in a liquid crystal layer of a liquid crystal device, and an underlayer on which the alignment layer is formed, the transparent substrate for a liquid crystal device includes a first surface and a second surface opposite to the first surface, the first surface being a surface included in the alignment layer, The second surface is a surface included in the underlayer, and the surface of the underlayer that contacts the alignment layer has a hardness of F or more in a pencil hardness test, the surface roughness Ra1 of the first surface is 20 nm or less, and the sum Ra1+Ra2 of the surface roughness Ra1 of the first surface and the surface roughness Ra2 of the second surface is 5 nm or more.
[0007] The light controlling sheet of the present invention includes a light controlling layer that is in contact with the first surface of the transparent substrate for a liquid crystal device and contains liquid crystal molecules. According to the above configuration, the alignment layer is formed on a base layer having a hardness of F or more in a pencil hardness test, so that the strength of the alignment layer can be increased. In addition, the sum Ra1+Ra2 of the surface roughness Ra1 of the first surface and the surface roughness Ra2 of the second surface is 5 nm or more. Therefore, the frictional force generated between the first surface and the second surface can be reduced, and defects in the alignment layer can be suppressed. In addition, while distributing the surface roughness on the first surface and the second surface, the surface roughness Ra1 of the first surface is set to 20 nm or less. Therefore, the alignment regulating force of the alignment layer can be maintained well while suppressing an excessive increase in haze caused by increasing the surface roughness of the second surface. Therefore, physical damage to the alignment layer provided in the transparent substrate for liquid crystal devices can be suppressed.
[0008] In the transparent substrate for a liquid crystal device, the second surface may have a surface roughness Ra2 of 100 nm or less. According to the above configuration, scattering at the second surface in a liquid crystal device using the transparent substrate for a liquid crystal device can be suppressed.
[0009] In the transparent substrate for a liquid crystal device, the sum Ra1+Ra2 of the surface roughness Ra1 of the first surface and the surface roughness Ra2 of the second surface may be 120 nm or less. According to the above configuration, it is possible to suppress scattering at the second surface in a liquid crystal device using the transparent substrate for a liquid crystal device, while maintaining the alignment restricting force of the alignment layer.
[0010] In the transparent substrate for a liquid crystal device, the underlayer includes a supporting substrate, a hard coat layer, a conductive layer and an alignment layer, and the hard coat layer is located between the supporting substrate and the alignment layer.
[0011] According to the above-mentioned configuration, even if the orientation layer is extremely thin and therefore has low strength, the orientation layer can be reinforced by the hard coat layer. In the transparent substrate for a liquid crystal device, the hard coat layer may contain a plurality of particles, and a diameter of the particle or an aggregate particle consisting of a plurality of the particles may be larger than the sum of a thickness of the hard coat layer, a thickness of the conductive layer, and a thickness of the alignment layer.
[0012] According to the above-mentioned configuration, the particles contained in the hard coat layer protrude from the first surface contained in the alignment layer, and thus the surface roughness can be controlled by adjusting the particle content.
[0013] In the transparent substrate for a liquid crystal device, the underlayer may be configured such that some of the particles contained in the underlayer protrude from at least one of the first surface and the second surface. According to the above-mentioned configuration, the surface roughness can be controlled by adjusting the content of particles contained in the underlayer.
[0014] In the transparent substrate for a liquid crystal device, the alignment layer may contain a silicone-based resin or a polyimide-based resin. According to the above-mentioned configuration, the strength of the alignment layer itself can be increased. Effect of the Invention
[0015] The present invention can suppress physical damage to the alignment layer provided on the transparent substrate for a liquid crystal device. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view illustrating a structure of a light controlling sheet according to a first embodiment. [Diagram 2] 1 is a cross-sectional view showing the structure of a transparent substrate for a liquid crystal device provided in a light controlling sheet of a first embodiment. [Diagram 3] FIG. 2 is a perspective view showing a state in which the transparent substrate for a liquid crystal device according to the first embodiment is stored. [Figure 4] 1 is a table showing the evaluation results of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A first embodiment of a transparent substrate for a liquid crystal device and a light controlling sheet will be described with reference to FIGS. 1 to 3. FIG. [Light control sheet] The light controlling sheet will be described with reference to FIG.
[0018] As shown in FIG. 1, the light-controlling sheet 10 includes a first substrate 11, a second substrate 12, and a light-controlling layer 13. The light-controlling layer 13 contains liquid crystal molecules. The light-controlling layer 13 is an example of a liquid crystal layer. In the light-controlling layer 13, the liquid crystal molecules may be held in a polymer network type (PNLC: Polymer Network Liquid Crystal) or a polymer dispersed type (PDLC: Polymer Dispersed Liquid Crystal). The liquid crystal molecules have negative dielectric anisotropy. In other words, the liquid crystal molecules are n-type.
[0019] Each of the first substrate 11 and the second substrate 12 is an example of a transparent substrate for a liquid crystal device. Each of the substrates 11, 12 is transparent to visible light. Each of the substrates 11, 12 includes an alignment layer. The alignment layer regulates the alignment direction of the liquid crystal molecules contained in the light-adjusting layer 13. Each of the substrates 11, 12 is in contact with the light-adjusting layer 13. In each of the substrates 11, 12, the surface in contact with the light-adjusting layer 13 is the first surface.
[0020] [Transparent substrates for liquid crystal devices] The transparent substrate for a liquid crystal device will be described with reference to FIG. 2 shows a cross-sectional structure of a first substrate 11, which is an example of a transparent substrate for a liquid crystal device. Note that while the second substrate 12 is positioned differently from the first substrate 11 in the thickness direction of the light adjusting sheet 10, the layers of the second substrate 12 are common to the layers of the first substrate 11. Therefore, in the following, the structure of the first substrate 11 will be described in detail, while a detailed description of the structure of the second substrate 12 will be omitted.
[0021] The first substrate 11 has a first surface 11S1 and a second surface 11S2 opposite to the first surface 11S1. The first surface 11S1 is a surface included in the alignment layer 21. The second surface 11S2 is a surface included in the underlayer 11A. The first surface 11S1 and the second surface 11S2 face each other.
[0022] The first substrate 11 includes an alignment layer 21 and an undercoat layer 11A on which the alignment layer 21 is formed. The undercoat layer 11A has a surface 11A1 in contact with the alignment layer 21 on the opposite side to the second surface 11S2. The undercoat layer 11A includes a support substrate 24, a hard coat layer 23, a conductive layer 22, and a slippery layer 26. The surface 11A1 is included in the conductive layer 22. The support substrate 24 has a first surface 24A and a second surface 24B. The first surface 24A and the second surface 24B face each other. The hard coat layer 23, the conductive layer 22, and the alignment layer 21 are laminated in this order on the first surface 24A. For convenience, the thickness of each layer is shown in FIG. 2 only diagrammatically.
[0023] The support substrate 24 is formed of, for example, a synthetic resin. The synthetic resin may be, for example, polyethylene terephthalate (PET) and polyethylene naphthalate (PEN). The support substrate 24 may have a thickness of, for example, 16 μm or more and 250 μm or less. The support substrate 24 is transparent to visible light. The support substrate 24 is not limited to a single-layer structure, and may have a multi-layer structure. When the support substrate 24 has a multi-layer structure, the support substrate 24 may include a first layer formed of a first material and a second layer formed of a second material different from the first material.
[0024] The hard coat layer 23 is located between the supporting substrate 24 and the conductive layer 22. The strength of the hard coat layer 23 is higher than the strength of the supporting substrate 24. Therefore, compared to when the underlayer 11A does not include the hard coat layer 23, the strength of the surface of the alignment layer 21 formed on the underlayer 11A is higher.
[0025] The hard coat layer 23 may be formed of, for example, an organic material, a silicon-based material containing silicon, or an inorganic material. The organic material is a synthetic resin, and may be, for example, a melamine-based resin, a urethane-based resin, or an acrylic resin. The silicon-based material may be a silane compound such as a silicone-based hard coat material. The inorganic material may be a metal oxide. The hard coat layer 23 may have a thickness of, for example, 1 μm or more and 10 μm or less. The hard coat layer 23 is transparent to visible light. The hard coat layer 23 is not limited to a single-layer structure, and may have a multilayer structure. When the hard coat layer 23 has a multilayer structure, the hard coat layer 23 may include a first layer formed from a first material and a second layer formed from a second layer different from the first material.
[0026] The hard coat layer 23 may also contain a plurality of particles 23P. The particles 23P may be added separately from the hard coat agent and may be made of a material different from the main component of the hard coat layer 23. The particles 23P may be formed of, for example, a synthetic resin or a silica-based inorganic material. The particles 23P may have a circular or elliptical cross-sectional shape or may have other shapes. The diameter D1 of at least some of the particles 23P among the plurality of particles 23P contained in the hard coat layer 23 is larger than the sum (T1+T2+T3) of the thickness T1 of the hard coat layer 23, the thickness T2 of the conductive layer 22, and the thickness T3 of the alignment layer 21 (D1>T1+T2+T3). Therefore, at least some of the particles 23P contained in the hard coat layer 23 protrude to the outside from the first surface 11S1. Therefore, the surface roughness of the first surface 11S1 is large. When the hard coat layer 23 includes particles 23P having an elliptical cross-sectional shape or particles 23P of various sizes, only some of the multiple particles 23P may protrude from the first surface 11S1.
[0027] The conductive layer 22 is located between the hard coat layer 23 and the alignment layer 21 in the thickness direction of the first substrate 11. Therefore, when a voltage is applied to the conductive layer 22, an electric field having a strength capable of driving the liquid crystal molecules is easily formed between the conductive layer 22 of the first substrate 11 and the conductive layer of the second substrate 12.
[0028] The conductive layer 22 is formed of, for example, a transparent conductive oxide (TCO). The TCO may be, for example, indium tin oxide (ITO), zinc oxide (ZnO), tin oxide (SnO2), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO). The conductive layer 22 may have a thickness of, for example, 5 nm or more and 100 nm or less. The conductive layer 22 is transparent to visible light.
[0029] The alignment layer 21 is a vertical alignment film. The alignment layer 21 aligns the liquid crystal molecules so that the long axis of the liquid crystal molecules is perpendicular to the plane on which the alignment layer 21 spreads. The angle formed by the alignment layer 21 and the long axis of the liquid crystal molecules may have a deviation from the right angle within a range that can be regarded as substantially a right angle. The alignment layer 21 is a silicone-based resin or a polyimide-based resin having a skeleton of a siloxane bond made of silicon and oxygen and an organic group bonded to the silicon. By forming the alignment layer 21 from these resins, the thermal stability and chemical stability of the alignment layer 21 can be improved. The alignment layer 21 is formed from, for example, polyamic acid, polyimide, polyvinyl alcohol (PVA), or the like. The surface of the alignment layer 21 may be subjected to a rubbing treatment. The thickness of the alignment layer 21 may be, for example, 20 nm or more and 500 nm or less. The alignment layer 21 is transparent to visible light.
[0030] A slippery layer 26 is formed on the second surface 24B of the support substrate 24. The synthetic resin may be, for example, any one of a melamine-based resin, a urethane-based resin, and an acrylic-based resin. The slippery layer 26 may have a thickness of, for example, 1 μm or more and 10 μm or less. The thickness of the slippery layer 26 is the thickness of the portion where the particles 26P are not located. The slippery layer 26 is transparent to visible light.
[0031] The lubricating layer 26 may include a plurality of particles 26P. The particles 26P may be formed of, for example, a synthetic resin. Alternatively, the particles 26P may be an inorganic material such as a silica-based material. The particles 23P contained in the hard coat layer 23 and the particles 26P contained in the lubricating layer 26 may be formed of the same material, or may be formed of different materials. The particles 26P are added separately from the coating material of the lubricating layer 26, and may be made of a material different from the main component of the lubricating layer 26. The particles 23P and 26P may be the same size, or may be different sizes. When the particles 26P are used as primary particles, the diameter D2 of at least a part of the particles 26P among the plurality of particles 26P contained in the lubricating layer 26 is larger than the thickness T4 of the lubricating layer 26 (D2>T4). When the plurality of particles 26P are aggregated, it is sufficient that at least a part of the aggregated particles has a diameter larger than the thickness T4 of the lubricating layer 26. Therefore, at least a part of the particles 26P or aggregated particles contained in the slippery layer 26 protrudes outward from the second surface 11S2. Therefore, the surface roughness of the second surface 11S2 is large.
[0032] Next, the characteristics of the first base material 11 will be described. The supporting substrate 24 is thin and highly flexible, and is therefore not suitable for a sheet-type manufacturing method. For this reason, a roll-to-roll method is used for manufacturing the first substrate 11 and the second substrate 12, and for manufacturing a light control sheet using the first substrate 11 and the second substrate 12. However, in the roll-to-roll method, defects occur in the alignment layer 21 due to friction between the wound substrates, pressing forces exerted on each other, and the like.
[0033] For this reason, the inventors increased the strength of the alignment layer 21 to suppress defects in the alignment layer 21. In addition, the surface roughness of the first surface 11S1 and the second surface 11S2 was increased to improve slipperiness and reduce friction. In this case, if only the surface roughness of the second surface 11S2 is increased, the haze becomes excessively large when the light controlling sheet 10 is in transparent operation. For this reason, the inventors found that the frictional force and the haze when in transparent operation can be reduced by distributing the surface roughness to the first surface 11S1 and the second surface 11S2.
[0034] In order to simultaneously increase the strength of the alignment layer 21 and distribute the surface roughness on the first surface 11S1 and the second surface 11S2, the first substrate 11 and the second substrate 12 satisfy at least the following conditions 1 to 3.
[0035] (Condition 1) Surface 11A1 of underlayer 11A has a hardness of F or more in a pencil hardness test. (Condition 2) The surface roughness Ra1 of the first surface 11S1 of the alignment layer 21 is more than 0 nm and is not more than 20 nm (0 nm <Ra1≦20nm)。
[0036] (Condition 3) The sum Ra1+Ra2 of the surface roughness Ra1 of the first surface 11S1 and the surface roughness Ra2 of the second surface 11S2 is 5 nm or more (5 nm≦Ra1+Ra2). Condition 1 will be described. The high hardness of the surface 11A1 of the underlayer 11A is realized by the hard coat layer 23 included in the underlayer 11A. The alignment layer 21 has a thickness of nanometer order and therefore has low strength. The first substrate 11 realizes high pencil hardness by the hard coat layer 23, so that the alignment layer 21 can have high strength while preferably providing a regulating force for regulating the alignment of liquid crystal molecules. If the hardness of the surface 11A1 of the underlayer 11A in the pencil hardness test is smaller than F, the strength of the alignment layer 21 decreases and defects in the alignment layer 21 are likely to occur due to frictional force or a pressing force in the normal direction of the first surface 11S1.
[0037] The pencil hardness test is performed according to a method conforming to JIS K 5600-5-4:1999 "General Test Methods for Paints-Part 5: Mechanical Properties of Coatings-Section 4: Scratch Hardness (Pencil Method)". The hardness of the surface 11A1 of the underlayer 11A is realized by the hard coat layer 23, so the pencil hardness of the surface of the hard coat layer 23 that contacts the conductive layer 22 is also F or more. The alignment layer 21 that contacts the surface 11A1 of the underlayer 11A has a pencil hardness lower than F. However, by setting the film thickness within an appropriate range, the alignment layer 21 is laminated on the hard coat layer 23 via the conductive layer 22, thereby achieving a pencil hardness of F or more.
[0038] The description will be given for Condition 2. The surface roughness Ra1 is the arithmetic mean roughness Ra of the first surface 11S1. By setting the surface roughness Ra1 of the first surface 11S1 within the range defined by Condition 2 and dispersing a part of the required surface roughness of the first surface 11S1 and the second surface 11S2, it is possible to suppress an excessive increase in haze caused by increasing the surface roughness Ra2 of the second surface 11S2. When the surface roughness Ra1 of the first surface 11S1 exceeds 20 nm (20 nm < Ra1), the alignment regulating force for aligning liquid crystal molecules of the alignment layer 21 partially decreases. In the portion where the alignment regulating force has decreased, the liquid crystal molecules are randomly oriented, so that it is visually recognized as a locally cloudy portion even during the transparent driving of the light control sheet 10. Furthermore, since the height difference of the uneven shape of the alignment layer 21 becomes large, an external force tends to concentrate on the top of the convex shape or the bottom of the concave shape. As a result, defects are likely to occur when an external force is applied to the alignment layer 21. By setting the surface roughness Ra1 of the first surface 11S1 within the range defined by Condition 2, it is possible to secure the alignment regulating force of the alignment layer 21 and appropriately control the haze of the light control sheet 10, and reduce the defects of the alignment layer 21. In addition, in order to disperse the surface roughness between the first surface 11S1 and the second surface 11S2, it is preferable that the surface roughness Ra1 of the first surface 11S1 is 2 nm or more.
[0039] The description will be given for Condition 3. The surface roughness Ra2 is the arithmetic mean roughness Ra of the second surface 11S2. By setting the sum Ra1 + Ra2 of the surface roughnesses of the first surface 11S1 and the second surface 11S2 within the range defined by Condition 3, it is possible to reduce the frictional force generated between the first surface 11S1 and the second surface 11S2. When the sum of the surface roughnesses Ra1 + Ra2 is less than 5 nm (Ra1 + Ra2 < 5 nm), the frictional force generated between the first surface 11S1 and the second surface 11S2 becomes large, and defects of the alignment layer 21 are likely to occur. In addition, as the contact area between the first surface 11S1 and the second surface 11S2 increases, blocking is likely to occur in which the first surface 11S1 and the second surface 11S2 adhere to each other and are difficult to peel off. As a result, when the film is pulled out from the film roll, the adhered first surface 11S1 and second surface 11S2 are forcibly peeled off, resulting in defects in the alignment layer 21.
[0040] Furthermore, it is preferable that the first base material 11 and the second base material 12 satisfy the following conditions 4 and 5 in addition to the conditions 1 to 3. (Condition 4) The surface roughness Ra2 of the second surface 11S2 including the easy-slip layer 26 is more than 0 nm and not more than 100 nm (0 <Ra2≦100nm)。
[0041] (Condition 5) The sum of the surface roughnesses Ra1 + Ra2 is 120 nm or less (Ra1 + Ra2 ≦ 120 nm). Condition 4 will be described. By setting the surface roughness Ra2 of the second surface 11S2 within the range specified by condition 4, the transparency of the light-controlling sheet 10 during transparent operation can be increased. The haze of the light-controlling sheet 10 during operation is preferably 20% or less. Depending on the application in which transparency during transparent operation is particularly required, it may be preferable for the haze to be 15% or less. If the haze during transparent operation exceeds 20%, it becomes difficult to identify objects with the naked eye through the light-controlling sheet 10. The haze of the light-controlling sheet 10 is determined by the external haze, which is scattering at the interface between the first substrate 11 and the air and the interface between the second substrate 12 and the air, and the internal haze caused by factors of the internal structure of the light-controlling sheet 10, such as the difference in refractive index between the particles 26P and the easy-slip layer 26 and the reduction in the alignment force of the alignment layer 21 as described above. Of these, the surface roughness of the second surface 11S2 changes the external haze. In other words, the scattering of visible light at the second surface 11S2 increases, and the haze of the first substrate 11 and the second substrate 12 increases. If the surface roughness Ra2 of the second surface 11S2 exceeds 100 nm, the transparency when the light controlling sheet 10 is driven in a transparent state can ensure practicality depending on the application, but the haze exceeds 15%.
[0042] Condition 5 will be described. If condition 1 is satisfied and the sum of the surface roughnesses Ra1+Ra2 of the first surface 11S1 and the second surface 11S2 is 120 nm, the alignment regulating force of the alignment layer 21 can be maintained while preventing the haze of the light controlling sheet 10 from increasing excessively in transparent operation. Specifically, the haze of the light controlling sheet 10 in transparent operation can be set to 15% or less. If the sum of the surface roughnesses Ra1+Ra2 of the first surface 11S1 and the second surface 11S2 exceeds 120 nm, the haze in transparent operation exceeds 15%.
[0043] [Effect] The function of the first base material 11 will be described with reference to FIG. When the light-adjusting sheet 10 is manufactured using the first substrate 11, the first substrate 11 is transported by a roll-to-roll device along the longitudinal direction of the first substrate 11. At this time, tension is applied to the first substrate 11 along the longitudinal direction, and the first substrate 11 is transported along the longitudinal direction while in contact with a guide roll provided in the roll-to-roll device. Therefore, when the first surface 11S1 of the first substrate 11 contacts the guide roll, friction occurs between the first surface 11S1 included in the alignment layer 21 and the guide roll. When the frictional force acting on the first surface 11S1 exceeds the strength of the first surface 11S1, a defect, which is physical damage, occurs in the portion of the alignment layer 21 where the frictional force acts. In addition, when the second surface 11S2 of the first substrate 11 contacts the guide roll, friction occurs between the second surface 11S2 included in the slippery layer 26 and the guide roll. The defect is a portion where the alignment layer 21 is missing, such as peeled off or damaged, and is no longer able to exert an alignment regulating force.
[0044] As shown in Figure 3, the first substrate 11 has a strip shape, and therefore when the first substrate 11 is transported from the roll-to-roll apparatus to another apparatus, or when the first substrate 11 is stored, the first substrate 11 has a roll shape wound around a core C.
[0045] When the first substrate 11 is wound around the core C, friction occurs between the first surface 11S1 and the second surface 11S2 of the first substrate 11. When the frictional force acting on the first surface 11S1 exceeds the strength of the first surface 11S1, defects occur in the portion of the alignment layer 21 on which the frictional force acts. In addition, when the first substrate 11 is transported, vibrations are applied to the first substrate 11, and friction occurs between a portion of the first surface 11S1 of the first substrate 11 and a portion of the second surface 11S2 in contact with the portion.
[0046] Furthermore, when the first substrate 11 is wound around the core C, pressure is generated in the thickness direction of the substrate. This is because the action of winding a substrate film such as the first substrate 11 around the core C is a repeated instantaneous action of pressing the substrate film against the core C. At this time, if the frictional force or pressing force acting on the first surface 11S1 exceeds the strength of the first surface 11S1, defects will occur in the portion of the alignment layer 21 where the frictional force or pressing force acts. Furthermore, the first substrate 11 may have a small amount of waviness. When the first substrate 11 is waviness-generated, the uneven portion where the waviness occurs presses the portion in contact with the uneven portion. In this case as well, if the frictional force or pressing force acting on the first surface 11S1 exceeds the strength of the first surface 11S1, defects will occur in the portion of the alignment layer 21 where the frictional force or pressing force acts.
[0047] In this regard, satisfaction of conditions 1 to 3 suppresses defects in the alignment layer 21. Furthermore, satisfaction of condition 2 can reduce the haze of the light controlling sheet 10 during transparent operation.
[0048] According to this embodiment, the following effects can be obtained. (1) Since the alignment layer 21 is formed on the underlayer 11A having a hardness of F or more in the pencil hardness test, the strength of the alignment layer 21 can be increased. In addition, the sum Ra1+Ra2 of the surface roughness Ra1 of the first surface 11S1 and the surface roughness Ra2 of the second surface 11S2 is 5 nm or more. Therefore, the frictional force generated between the first surface 11S1 and the second surface 11S2 can be reduced, and damage to the alignment layer 21 can be suppressed. In addition, while distributing the surface roughness to the first surface 11S1 and the second surface 11S2, the surface roughness Ra1 of the first surface 11S1 is set to 20 nm or less. Therefore, the alignment regulating force of the alignment layer 21 can be maintained well while suppressing an excessive increase in haze caused by increasing the surface roughness of the second surface 11S2. Therefore, physical damage to the alignment layer 21 provided in the light control sheet 10 can be suppressed.
[0049] (2) Since the surface roughness of the second surface 11S2 is 100 nm or less, in the light controlling sheet 10 using the first base material 11 and the second base material 12, scattering on the second surface 11S2 can be suppressed.
[0050] (3) Since the sum of the surface roughnesses Ra1+Ra2 is 120 nm or less, the orientation control force of the orientation layer 21 is maintained while light scattering on the second surface 11S2 in the light-controlling sheet 10 using the first substrate 11 and the second substrate 12 can be suppressed.
[0051] (4) The hard coat layer 23 having a hardness of F or more in a pencil hardness test is located between the supporting substrate 24 and the alignment layer 21. Therefore, even if the alignment layer 21 is extremely thin and therefore has low strength, the alignment layer 21 can be reinforced by the hard coat layer 23.
[0052] (5) The diameter of at least some of the particles 23P or aggregated particles made of a plurality of particles 23P contained in the hard coat layer 23 is larger than the sum of the thickness of the hard coat layer 23, the thickness of the conductive layer 22, and the thickness of the alignment layer 21. Therefore, the particles 23P or aggregated particles made of a plurality of particles 23P contained in the hard coat layer 23 protrude from the first surface 11S1 contained in the alignment layer 21. This makes it possible to increase the surface roughness Ra1 of the first surface 11S1. In addition, it is possible to control the surface roughness Ra1 by adjusting the content of the particles 23P.
[0053] (6) Since the alignment layer 21 contains a silicone-based resin or a polyimide-based resin, the thermal stability and chemical stability of the alignment layer 21 can be improved. [Variations] The above embodiment can be modified as follows. The following modifications and the above embodiment may be combined and implemented.
[0054] [Base layer] The underlayer 11A in the above embodiment includes a hard coat layer 23. Alternatively, if the first surface 11S1 satisfies conditions 1 and 2, the underlayer 11A does not need to include the hard coat layer 23. In this case, for example, the support substrate 24 may have a high strength such that the first surface 11S1 has a pencil hardness of F or more.
[0055] The underlayer 11A in the above embodiment includes particles 23P contained in the hard coat layer 23. Alternatively, if the surface roughness Ra1 of the first surface 11S1 satisfies conditions 2 and 3, the underlayer 11A does not need to include particles 23P. In this case, it is sufficient that the alignment layer 21, the conductive layer 22, and the support substrate 24 have a surface roughness large enough that the surface roughness R1a of the first surface 11S1 satisfies conditions 2 and 3.
[0056] The base layer 11A in the above embodiment includes a slippery layer 26. Alternatively, as long as the second surface 11S2 satisfies at least condition 3, the base layer 11A does not need to include the slippery layer 26. In this case, for example, it is sufficient that the support substrate 24 includes the second surface 11S2 and the surface roughness Ra2 of the second surface 11S2 satisfies condition 3. In addition, it is preferable that the second surface 11S2 included in the support substrate 24 satisfies conditions 4 and 5.
[0057] Also, a separate film such as a protective film may be attached to the second surface 24B side of the supporting substrate 24 to satisfy the surface roughness Ra2 of 11S2. In this case, although it is necessary to peel off the protective film when using the light control film, the design freedom of the supporting substrate 24 can be increased.
[0058] The undercoat layer 11A in the above embodiment includes particles 26P contained in the slippery layer 26. Alternatively, as long as the surface roughness Ra2 of the second surface 11S2 at least satisfies condition 3, the undercoat layer 11A does not need to include particles 26P. In this case, it is sufficient that the support substrate 24 has a surface roughness large enough to cause the surface roughness R2a of the second surface 11S2 to fall within the range of condition 3.
[0059] The conductive layer 22 may be located between the support substrate 24 and the hard coat layer 23 in the thickness direction of the underlayer 11A. Even in this case, since the underlayer 11A has the hard coat layer 23, it is possible to obtain an effect similar to that of (1) above. In this case, since the distance between the conductive layer 22 and the first surface 11S1 is expanded in the thickness direction of the underlayer 11A, a high voltage may be required to drive the liquid crystal molecules.
[0060] [Light control sheet] In the above embodiment, the liquid crystal device is embodied as a reverse-type light control sheet 10 in which the linear transmittance is low when a current is applied and high when a current is not applied. Alternatively, the liquid crystal device may be embodied as a normal-type light control sheet in which the linear transmittance of visible light is high when a current is applied and low when a current is not applied. Examples of normal-type light control sheets include a light control sheet having a light control layer containing p-type liquid crystal between a pair of alignment layers having a horizontal alignment regulating force, and a light control sheet having a light control layer containing n-type liquid crystal between a pair of alignment layers having a vertical alignment force. A light control sheet having a light control layer containing n-type liquid crystal has a first substrate, a light control layer, and a second substrate between a pair of polarizing plates.
[0061] [Liquid crystal devices] The liquid crystal device to which the transparent substrate for a liquid crystal device of the present disclosure is applied is not limited to the above-mentioned light control sheet, as long as it has an alignment layer. For example, it may be a liquid crystal display device.
[0062] [Example] Examples and comparative examples will be specifically described with reference to Fig. 4. Note that the present invention is not necessarily limited to these examples.
[0063] [Example 1] <Preparation of easy-slip layer> First, a paint for the easy-slip layer was prepared to form the easy-slip layer. 0.02 wt% of acrylic particles (Techpolymer SSX-102, Sekisui Chemical Co., Ltd.) with an average particle size of 2 μm was added to a highly crosslinked acrylic hard coat agent (Lioduras LCH6701, Toyochem Co., Ltd.). Furthermore, methyl ethyl ketone was added to the hard coat paint to adjust the solid concentration including the acrylic particles to 50 wt%.
[0064] A film made of polyethylene terephthalate (PET) (Cosmoshine A4300, manufactured by Toyobo Co., Ltd.) (Cosmoshine is a registered trademark) was prepared. The total thickness of the PET film was 125 μm. The prepared coating material for the easy-slip layer was applied to one side of the PET film using a gravure coater. At that time, the coating material was applied so that the thickness of the part of the hardened easy-slip layer where no acrylic particles were present was 1.5 μm. The PET film to which the coating material for the easy-slip layer was applied was dried at a temperature of 80°C for 1 minute, and then 300 mJ / cm was applied using a high-pressure mercury lamp. 2 The PET film on which the lubrication layer was formed was then wound up in-line to obtain a film roll with the lubrication layer attached.
[0065] <Preparation of hard coat layer> Next, a hard coat layer was formed on the side of the film with the easy-slip layer opposite to the side on which the easy-slip layer was formed. (1st paint) The following was adjusted. 0.02% by weight of acrylic particles (Techpolymer SSX-102, Sekisui Chemical Co., Ltd.) with an average particle size of 2 μm was added to a highly cross-linked acrylic resin hard coat agent (Lioduras LCH6701, Toyochem Co., Ltd.). Furthermore, methyl ethyl ketone was added to the hard coat paint to adjust the solids concentration to 50% by weight.
[0066] The prepared hard coat paint was applied to the side of the film with the easy-slip layer opposite to the side on which the easy-slip layer was formed, using a gravure coater. At that time, the paint was applied so that the thickness of the part of the hard coat layer where no acrylic particles were present was 1.5 μm. The PET film with the easy-slip layer to which the hard coat paint was applied was dried at a temperature of 60 degrees for 1 minute, and then 300 mJ / cm was applied using a high-pressure mercury lamp. 2 The film on which the hard coat layer was formed was then wound up in-line to obtain a film roll in which the film with the hard coat layer was wound up.
[0067] <Preparation of conductive layer> Next, a conductive layer was formed on the hard coat layer. A roll sputtering device equipped with a mixed sintered target of indium oxide (90% by weight) and tin oxide (10% by weight) was used to form the conductive layer. A film roll was set in this roll sputtering device, and the inside of the device was evacuated to 0.4 Pa. Then, argon gas and oxygen gas were introduced into the device. Then, the substrate temperature, which is the temperature applied to the film, was set to 40°C, and the pressure was set to 0.4 Pa to perform film formation. As a result, a conductive layer with a thickness of 50 nm was formed on the underlayer. Furthermore, the PET film on which the conductive layer was formed was heat-treated at a temperature of 140°C for 90 minutes to crystallize the conductive layer. This film with the conductive layer was wound into a roll.
[0068] <Preparation of alignment layer> Next, an alignment layer was laminated on the conductive layer. A coating solution for forming an alignment layer was obtained by adjusting a coating material for an alignment layer (Sunever SE-H682, manufactured by Nissan Chemical Co., Ltd.) (Sunever is a registered trademark) whose main material is polyamic acid, using a solvent so that the solid content was 5% by weight. In the solvent, the weight ratio of propylene glycol monomethyl ether and γ-butyl lactone was set as follows.
[0069] Propylene glycol monomethyl ether:gamma-butyl lactone=8:2 The film with the conductive layer was pulled out from the film roll, and the paint for the alignment layer was applied onto the conductive layer using a roll coater. The film with the paint for the alignment layer applied was then dried at a temperature of 150 degrees for 5 minutes to form an alignment layer with a thickness of 100 nm. As a result, the paint mainly made of polyamic acid becomes an alignment layer with polyimide as the main skeleton. The film with the alignment layer laminated thereon was wound up into a roll and collected. As a result, a film including a base layer was obtained. The film roll with the film with the base layer wound up was prepared as a set of two rolls. The transparent substrate for liquid crystal devices was stored for 7 days in a clean room maintained at 23°C and a relative humidity of 50% RH. This film with the base layer was used as a sample of the film alone.
[0070] <Characteristics of transparent substrates for liquid crystal devices> The film with the undercoat layer was pulled out from the film roll, cut to a predetermined size, and then subjected to the following evaluations.
[0071] (A) Measurement of surface roughness Ra1 of the first surface The arithmetic mean roughness of the first surface including the alignment layer was measured using a white light interferometer (VertScan R3300h Lite, manufactured by Ryoka Systems Co., Ltd.). In this case, a rectangular field of view having a width of 1.408 mm and a length of 1.885 mm was used as the measurement target for the arithmetic mean roughness. The arithmetic mean roughness was measured by a method conforming to JIS B 0601:2013. This arithmetic mean roughness was taken as the surface roughness Ra1 of the first surface. The surface roughness Ra1 of the first surface in Example 1 was 4 nm.
[0072] (B) Measurement of surface roughness Ra2 of the second surface The surface roughness Ra2 of the second surface including the lubrication layer 26 was measured. The surface roughness Ra2 of the second surface was measured in the same manner as the surface roughness Ra1 of the first surface. The surface roughness Ra2 of the second surface in Example 1 was 3 nm.
[0073] (C) The sum of surface roughness Ra1 and surface roughness Ra2 The sum of the surface roughness Ra1 of the first surface and the surface roughness Ra2 of the second surface was determined. The sum of the surface roughness Ra1 and the surface roughness Ra2 in Example 1 was 7 nm.
[0074] (D) Pencil hardness measurement A pencil hardness test was carried out on the surface of the underlayer that contacted the alignment layer. The method used was in accordance with JIS K 5600-5-4:1999 "General test methods for coating films - Part 5: Mechanical properties of coating films - Section 4: Scratch hardness (pencil method)". The pencil hardness in Example 1 was H.
[0075] (E) Appearance of film roll The film roll was visually observed to see whether the front and back of the substrate were stuck or bulged. When the film roll was deformed compared to a standard film roll in which the substrate was not stuck or bulged, it was determined that the substrate was stuck or bulged. For example, the sticking of the front and back of the substrate is confirmed as an excessively transparent area compared to the surrounding area when viewed from the front of the film roll in which the surface of the substrate is visible. Or, when the end face of the wound substrate is viewed from the side of the film roll in which the end face of the wound substrate is visible, it is determined that the substrate is stuck or bulged when the end face of the substrate is not wound in a circular shape close to a perfect circle but wound in a polygonal shape. If the substrate is stuck or bulged, the substrate itself may be deformed when the substrate is pulled out of the film roll, or in the worst case, the film may be torn. If any sticking or swelling was observed on the front and back of the substrate, it was rated as defective (NG), and if no sticking or swelling was observed on the front and back of the substrate, it was rated as excellent (OK).
[0076] <Preparation of light control sheet> The film roll with the undercoat layer was stored in a clean room maintained at a temperature of 23°C and a relative humidity of 50% for 7 days, after which the film roll was transported to a location for the next process.
[0077] A light-control layer was prepared between a pair of films with an alignment layer. 17.5 parts by weight of an ultraviolet-curing coating agent (Loctite 3736, manufactured by Henkel) and 17.5 parts by weight of 1,9-nonanediol methacrylate were mixed. 65 parts by weight of an n-type liquid crystal composition (MLC-6608, manufactured by Merck) was further mixed into this mixture to obtain a coating material for the light-control layer.
[0078] Bead spacers, the main component of which is divinylbenzene and has a particle size of 6 μm, were dispersed in isopropyl alcohol. This spacer dispersion agent was applied to the first surface of the film with the alignment layer so that the area occupied by the bead spacers was 1.5%. The film coated with the spacer dispersion agent was then dried at a temperature of 100 degrees and wound up.
[0079] The film with the alignment layer, on which the bead spacers were scattered, was pulled out from the first film roll, which was wound up, and the light-controlling layer paint was applied onto the alignment layer using a die head coater. Next, in a nitrogen atmosphere, the light-controlling layer paint was irradiated with ultraviolet light from a high-pressure mercury lamp that cuts off light rays with wavelengths of 350 nm or less, to harden the light-controlling layer paint. At this time, the illuminance was set to 20 mW / cm. 2 The irradiation time was 30 seconds and the temperature was 25°C. Furthermore, the film with the alignment layer pulled out from the second film roll was overlapped and bonded to the light-control layer. This resulted in a light-control sheet in which the light-control layer was sandwiched between a pair of films with alignment layers.
[0080] Example 2 In Example 1, the amount of acrylic particles added to the easy-slip layer was changed to 1.00% by weight, but the film alone and the light-adjusting sheet were produced in the same manner as in Example 1. In Example 2, the surface roughness Ra1 of the first surface was 5 nm, the surface roughness Ra2 of the second surface was 40 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 45 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0081] Example 3 In Example 1, the amount of acrylic particles added to the easy-slip layer was changed to 3.00% by weight, but the film alone and the light-adjusting sheet were produced in the same manner as in Example 1. In Example 3, the surface roughness Ra1 of the first surface was 4 nm, the surface roughness Ra2 of the second surface was 97 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 101 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0082] Example 4 In Example 1, a film alone and a light control sheet were produced in the same manner as in Example 1, except that the acrylic particles in the hard coat layer were changed to 0.025% by weight. In Example 4, the surface roughness Ra1 of the first surface was 6 nm, the surface roughness Ra2 of the second surface was 5 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 11 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0083] Example 5 In Example 1, the amount of acrylic particles in the hard coat layer was changed to 0.025% by weight, and the amount of acrylic particles added to the easy-slip layer was changed to 1.00% by weight. A film and a light-controlling sheet were produced in the same manner as in Example 1. In Example 5, the surface roughness Ra1 of the first surface was 9 nm, the surface roughness Ra2 of the second surface was 35 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 44 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0084] Example 6 In Example 1, the amount of acrylic particles in the hard coat layer was changed to 0.025% by weight, and the amount of acrylic particles added to the easy-slip layer was changed to 3.00% by weight. A film and a light-controlling sheet were produced in the same manner as in Example 1. In Example 6, the surface roughness Ra1 of the first surface was 6 nm, the surface roughness Ra2 of the second surface was 100 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 106 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0085] Example 7 In Example 1, a film alone and a light control sheet were produced in the same manner as in Example 1, except that the acrylic particles in the hard coat layer were changed to 0.45% by weight. In Example 7, the surface roughness Ra1 of the first surface was 18 nm, the surface roughness Ra2 of the second surface was 5 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 23 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0086] Example 8 In Example 1, the amount of acrylic particles in the hard coat layer was changed to 0.45% by weight, and the amount of acrylic particles added to the easy-slip layer was changed to 1.00% by weight. A film and a light-controlling sheet were produced in the same manner as in Example 1. In Example 8, the surface roughness Ra1 of the first surface was 17 nm, the surface roughness Ra2 of the second surface was 50 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 67 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0087] Example 9 In Example 1, the amount of acrylic particles in the hard coat layer was changed to 0.45% by weight, and the amount of acrylic particles added to the easy-slip layer was changed to 3.00% by weight. A film and a light-controlling sheet were produced in the same manner as in Example 1. In Example 9, the surface roughness Ra1 of the first surface was 19 nm, the surface roughness Ra2 of the second surface was 99 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 118 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0088] Example 10 In Example 1, the acrylic resin hard coat layer paint was Second paint instead of first paint A film and a light control sheet were produced in the same manner as in Example 1, except that a coating agent (Lioduras TP-203X, manufactured by Toyo Ink Co., Ltd.) was used, no acrylic particles were added, and the amount of acrylic particles added to the easy-slip layer was changed to 3.00% by weight. The acrylic resin used in Example 10 had a lower degree of crosslinking than the acrylic resin used in Example 1. In Example 10, the surface roughness Ra1 of the first surface was 2 nm, the surface roughness Ra2 of the second surface was 98 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 100 nm. The pencil hardness of the surface of the undercoat layer was HB.
[0089] Example 11 In Example 1, the amount of acrylic particles added to the easy-slip layer was changed to 4.00% by weight, but the film alone and the light-adjusting sheet were produced in the same manner as in Example 1. In Example 11, the surface roughness Ra1 of the first surface was 4 nm, the surface roughness Ra2 of the second surface was 125 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 129 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0090] Example 12 In Example 1, the film alone and the light control sheet were produced in the same manner as in Example 1, except that the acrylic particles were not added to the hard coat layer and the amount of the acrylic particles added to the easy-slip layer was changed to 3.00% by weight. In Example 12, the surface roughness Ra1 of the first surface was 3 nm, the surface roughness Ra2 of the second surface was 98 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 101 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0091] (Example 13) In Example 1, the film alone and the light control sheet were produced in the same manner as in Example 1, except that the acrylic particles were not added to the hard coat layer, and the amount of the acrylic particles added to the easy-slip layer was changed to 0.10% by weight. In Example 13, the surface roughness Ra1 of the first surface was 2 nm, the surface roughness Ra2 of the second surface was 5 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 7 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0092] Comparative Example 1 In Example 1, a film alone and a light control sheet were produced in the same manner as in Example 1, except that acrylic particles were not added to either the hard coat layer or the easy-slip layer. In Comparative Example 1, the surface roughness Ra1 of the first surface was 1 nm, the surface roughness Ra2 of the second surface was 2 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 3 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0093] Comparative Example 2 In Example 1, the acrylic particles in the hard coat layer were changed to 0.839% by weight, and the acrylic particles were not added to the easy-slip layer. A film and a light-controlling sheet were produced in the same manner as in Example 1. In Comparative Example 2, the surface roughness Ra1 of the first surface was 31 nm, the surface roughness Ra2 of the second surface was 2 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 33 nm. In addition, the pencil hardness of the surface of the undercoat layer was H.
[0094] Comparative Example 3 In Example 1, a film alone and a light-controlling sheet were produced in the same manner as in Example 1, except that a hard coat layer was not provided, a conductive layer and an orientation layer were provided on the support substrate, and the amount of acrylic particles added to the easy-slip layer was 3.00% by weight. In Comparative Example 3, the surface roughness Ra1 of the first surface was 2 nm, the surface roughness Ra2 of the second surface was 98 nm, and the sum of the surface roughness Ra1 and the surface roughness Ra2 was 100 nm. In addition, the pencil hardness of the surface of the undercoat layer was 2B.
[0095] <Evaluation of light control sheets> Evaluations were carried out on the light controlling sheets of Examples 1 to 13 and Comparative Examples 1 to 3. The number of defects and haze of each light controlling sheet are shown in FIG.
[0096] (F) Haze measurement The haze of the transparent substrates for liquid crystal devices of Examples 1 to 13 and Comparative Examples 1 to 3 was measured according to JIS K 7136:2000 "Determination of haze of plastics-transparent materials". Ta.
[0097] (G) Haze measurement A3-sized test pieces were cut out from the light-controlling sheets of the examples and comparative examples. In each test piece, a part of each ITO layer was exposed to the outside, thereby forming a terminal for applying a voltage to the light-controlling sheet. Then, for each test piece, the haze was measured without voltage being applied. In addition, the exposed conductive layer was clamped with an alligator clip, and an AC voltage of 40 V at a frequency of 60 Hz was applied between the pair of conductive layers using an AC power supply device (PCR-3000WE, manufactured by Kikusui Electronics Co., Ltd.). Then, while applying the voltage, the haze was measured using a haze meter (NDH-7000SP manufactured by Suga Test Instruments Co., Ltd.). When measuring the haze, a method conforming to JIS K 7136:2000 "Determination of haze of plastics - transparent materials" was used. A haze of 15% or less when driven transparent was considered excellent. Ta .
[0098] (H) Number of defects in the light control film The light-control film was cut into samples measuring 1m x 1m. No driving voltage was applied to the samples, and they were irradiated with light from a three-wavelength light source of 1000 lux or more, and the number of defects was visually counted. Defective areas were defined as areas with a maximum diameter of 2mm or more that appeared cloudier than the surroundings when the light-control film was visually inspected. If the alignment layer had a large number of defects, the alignment control force would be insufficient during transparent operation, causing the liquid crystal molecules to be randomly aligned rather than vertically aligned. This causes the incident light to scatter, resulting in the appearance of cloudiness. Those with fewer than 50 defects were rated as excellent, and those with 50 or more defects were rated as poor.
[0099] (comprehensive evaluation) (H) Rating Price If the quality is excellent, it is judged as a good product. 、 (H) Rating Price Products that were defective were deemed defective.
[0100] <Evaluation Results> In Comparative Example 1, the sum of the surface roughnesses Ra1+Ra2 is 3 nm, which does not satisfy condition 3. Since phenomena such as sticking and swelling were confirmed in the rolled form, it was evaluated as defective. This is thought to be because the first and second surfaces were too smooth, causing sticking on the front and back of the substrate. In addition, the number of defects in the alignment layer was 50 or more, and it was evaluated as defective due to the large number of defects. This is thought to be because sticking occurred on the front and back of the substrate, and peeling of the alignment layer occurred when the substrate was pulled out. Therefore, in the overall evaluation, the substrate and light-control sheet of Comparative Example 1 were evaluated as defective.
[0101] In Comparative Example 2, the surface roughness Ra1 of the first surface is 30 nm, which does not satisfy Condition 2. In addition, when the transparent substrate for liquid crystal devices is pulled out from this film roll to produce a light-adjusting sheet, the number of defects in the transparent substrate for liquid crystal devices was large, and opaque parts and transparent parts were mixed. For this reason, it was not possible to obtain a sample with a uniform haze that could be measured with a haze meter, and it was difficult to measure optical properties such as haze. For this reason, it was determined that the measurement was impossible. In addition, the number of defects in the light-adjusting sheet was 50 or more, and it was determined to be defective due to the large number of defects. This is thought to be because the alignment regulating force of the alignment layer was reduced due to the large surface roughness Ra1 of the first surface. For this reason, the overall evaluation was determined to be defective.
[0102] Comparative Example 3 does not have a hard coat layer, so the hardness of the first surface is low and does not satisfy condition 1. In addition, when the transparent substrate for liquid crystal devices was pulled out from this film roll to produce a light-adjusting sheet, the transparent substrate for liquid crystal devices had many defects, so the transparent portions were selected and the haze was measured. It was clear that the number of defects in the light-adjusting sheet was 50 or more, which was too many, so counting was abandoned. This is thought to be because the strength of the alignment layer was low, and the alignment layer peeled off when the transparent substrate for liquid crystal devices was rolled up, transported, or pulled out. For this reason, the overall evaluation was determined to be defective. [Explanation of symbols]
[0103] 10. Light-adjusting sheet 11...First base material 11A…base layer 12…Second base material 13...Photochromic layer 21...Alignment layer 22...Conductive layer 23...Hard coat layer 24...Supporting base material 25...adhesive layer 26…Easy layer
Claims
1. A transparent substrate for a liquid crystal device, comprising: an alignment layer for regulating an alignment direction of liquid crystal molecules contained in a liquid crystal layer of a liquid crystal device; and a base layer on which the alignment layer is formed, A first surface and a second surface opposite the first surface, The first surface is a surface included in the alignment layer, the second surface is a surface included in the underlayer, the surface of the underlayer in contact with the orientation layer has a hardness of F or more in a pencil hardness test; The first surface has a surface roughness Ra1 of 2 nm or more and 20 nm or less, and the second surface has a surface roughness Ra2 of 3 nm or more and 100 nm or less, The sum of the surface roughness Ra1 of the first surface and the surface roughness Ra2 of the second surface (Ra1+Ra2) is 5 nm or more and 120 nm or less. Transparent substrate for liquid crystal devices.
2. A transparent substrate for a liquid crystal device, comprising: an alignment layer that regulates the alignment direction of liquid crystal molecules contained in a liquid crystal layer of a liquid crystal device; and a base layer on which the alignment layer is formed, A first surface and a second surface opposite the first surface, The first surface is a surface included in the alignment layer, the second surface is a surface included in the underlayer, the surface of the underlayer in contact with the orientation layer has a hardness of F or more in a pencil hardness test; The first surface has a surface roughness Ra1 of 20 nm or less, The sum Ra1 + Ra2 of the surface roughness Ra1 of the first surface and the surface roughness Ra2 of the second surface is 5 nm or more, the underlayer includes a supporting substrate, a hard coat layer, a conductive layer, and a lubricating layer having the second surface, the hard coat layer is located between the supporting substrate and the conductive layer, The hard coat layer and the lubricity layer contain a plurality of particles, the diameter of the particle or the aggregated particle consisting of a plurality of the particles contained in the hard coat layer is larger than the sum of the thickness of the hard coat layer, the thickness of the conductive layer and the thickness of the alignment layer, and the diameter of the particle or the aggregated particle consisting of a plurality of the particles contained in the lubrication layer is larger than the thickness of the lubrication layer; The particles or the aggregated particles contained in the hard coat layer protrude from the first surface, and the particles or the aggregated particles contained in the lubrication layer protrude from the second surface. Transparent substrate for liquid crystal devices.
3. The alignment layer contains a silicone resin or a polyimide resin. The transparent substrate for a liquid crystal device according to claim 1 or 2.
4. A transparent substrate for a liquid crystal device according to any one of claims 1 to 3, A light control layer is provided in contact with the first surface of the transparent substrate for a liquid crystal device and contains liquid crystal molecules. Dimming sheet.
Citation Information
Patent Citations
Liquid crystal optical element
JP1995239484A
Liquid crystal display element
JP1995270763A
Transparent electrode substrate and liquid crystal display element formed by using the same
JP1998111500A
Liquid crystal display element and electronic instrument
JP2001221998A
Method for manufacturing liquid crystal alignment layer and liquid crystal display element
JP2006154158A